Scaling up COMFA+Fish: Report for Sensory Panels IV and V. - Mudege, Netsayi; Ragsdale, Kathleen; Tolar-Peterson, Terezie; Muzungaire, Lizzy; Banda, Sylvia; Roman, Katie; Burdine, Madeline; Chileya, Agness (Mississipi State University, 2025)
In sensory panel IV (Adults), The ComFA+Fish strawberry flavor instant porridge is a market-leading product with exceptional sensory appeal and usability. Its nearly universal positive ratings on texture and flavor can set a high benchmark to improve the other variants. The ComFA+ strawberry porridge is due to its high acceptability. There is a need to improve plain porridge and the Vanilla+Kapenta variants in terms of flavor and texture. Insights from strawberry's success— such as flavor balancing and texture consistency—could be applied to refine the other variants. In sensory panel V (infants), the ComFA+Fish strawberry flavor instant porridge has the strongest appeal among infants, followed by the vanilla flavor. Strawberry porridge should be prioritized for launch due to its universal appeal among infants and, thus, suitable for mainstream adoption. Vanilla porridge can also be promoted as an option for kids as it performs well across T1, T2 and T3. Vanilla porridge is a big contender for infants and children who like subtle flavors. The ComFA+Fish vanilla flavor extra kapenta porridge must be reformulated to improve broader acceptability. Reducing portion sizes to reduce food waste and encourage children to consume porridge fully may be critical.